Resistance of Santa Inês and Ile de France suckling lambs to gastrointestinal nematode infections. - Rocha, Raquel A; Amarante, Alessandro F T; Bricarello, Patrizia A (My University, 2005)
A trial was carried out to determine the resistance to natural infection by gastrointestinal nematodes in 12 Santa Inês and nine Ile de France lambs before weaning. Faecal samples were obtained for faecal nematode egg counts (FEC). Blood samples were collected to determine packed cell volume (PCV), total plasma protein levels and peripheral eosinophil counts. Most Ile de France lambs (77.8%) were treated with an anthelmintic at 43 days of age, while 50% off Santa Inês lambs were treated at weaning, 57 days of age. The mean PCV values were normal in Santa Inês lambs, while in Ile de France lambs showed lower values reaching 22.3% at 43 days of age. The lowest mean plasma protein values were observed in Ile de France lambs (4.13 g/dl) at 43 days of age and in Santa Inês lambs (5.0 g/dl) at 57 days of age. Before weaning, Santa Inês lambs were susceptible to natural infections by gastrointestinal nematodes but with a greater capacity to stand the adverse effects of parasitism compared to Ile de France lambs.
Keywords: animal; animal disease; cattle; cattle disease; cellular immunity; disease predisposition; feces; female; Haemonchus; immunology; intestine infection; isolation and purification; male; nematodiasis; parasitology; suckling; Animals; Animals, Suckling; Cattle; Cattle Diseases; Disease Susceptibility; Feces; Female; Immunity, Cellular; Intestinal Diseases, Parasitic; Male; Nematode Infections